Mathematical model of quarantine and recurrent infections with a deceased disposition - Anjali; Singh, Manoj Kumar (Fırat Evirgen, 2026)
The COVID-19 pandemic impacted every element of human existence. It emerged as one of the most essential worldwide catastrophes in recent memory. The virus first appeared in late 2019. Its spread across national boundaries triggered a series of events that disrupted economies and healthcare systems, resulting in significant loss and suffering. The handling and disposal of infected dead bodies also played a role in the spread of the virus. This article investigates the local and global stability, as well as the transcritical bifurcation, of the mathematical model, including the deceased compartment. Additionally, the sensitivity and threshold analysis of the proposed mathematical model, which categorizes individuals into eight classes: susceptible, exposed, quarantined, symptomatic, asymptomatic, hospitalized, recovered, and deceased, is examined. Numerical simulation has supported the model in validation.
Keywords: Biological Mathematics; Biyolojik Matematik